Women in Whistler’s Images of Chelsea and the Thames - Patricia de Montfort (British Art Studies, 2022)
Women are an active, if often low-key, presence in Whistler’s Thames images, from ghostly figures of models and fashionable strolling women to the small traders who populated the streets near his home in Chelsea. Women shopped for their families; they worked outside the home as servants, nursemaids, shop assistants, and in family trades. They travelled along the river daily and criss-crossed its banks in a changing cityscape in which new spaces for leisure were being opened up. They sought a living in a night-time world of entertainment venues like Vauxhall Gardens and Cremorne that could lead to exploitation, disease, and an early grave. This world beyond Whistler’s Chelsea homes, overseen during the 1860s by his model and partner, Joanna Hiffernan (and by his mother, Anna Whistler for a time), is often overlooked. Moreover, Whistler’s suggestion that the presence of tiny, anonymised female figures in works like Variations in Pink and Grey: Chelsea and Cremorne Gardens, No. 2 was merely about colour and establishing a balance of decorative elements invites fresh analysis. This essay takes as its starting point women’s presences in Whistler’s riverside home and family circle before venturing outdoors to explore the world they inhabited along the Thames at Chelsea. It considers such questions as: how did women experience the contemporary redevelopment of the river? How did they occupy its adjacent streets and public spaces? Drawing upon examples of Whistler’s Thames subjects from the 1870s and the work of chroniclers of social change like Chelsea photographer James Hedderly (1815–1885), it examines the world of women along the river in the context of visual, literary, and socio-economic discourses of the period. It seeks to give voice to their presence beneath the quiet surface of Whistler’s images and how, as “involuntary neighbours”, they made sense of the watery, arterial world of London’s celebrated river.